Would a new definition and classification of nocturia and nocturnal polyuria improve our management of patients? ICI‐RS 2014. Issue 2 (10th April 2015) - Bosch, J.L.H. Ruud; Everaert, Karel; Weiss, Jeffrey P.; Hashim, Hashim; Rahnama'i, M. Sajjad; Goessaert, An‐Sofie; Aizen, Joshua
Abstract : The following is a report of the proceedings of the Nocturia Think Tank sessions of the annual International Consultation on Incontinence—Research Society, which took place September 22–24, 2014 in Bristol, UK. The report is organized into sections pertaining to the main topic of discussion focussing on the question as to whether a new definition and classification of nocturia and nocturnal polyuria would improve the outcome of management in our patients. First, discussions identified theoretical and practical shortcomings of current definitions. Secondly, the utility of several nocturnal polyuria definitions was tested in a real life population in relation to the symptom nocturia, in order to display weaknesses of these definitions. Thirdly, we explored in a clinical population the utility of bladder diary based parameters by asking the question: when nocturia improves, which of these parameters improve most? Based on the above explorations the Think Tank summarized elements of the current definitions that need reconsideration and suggests proposals for further research to reach more practical and more clinically meaningful definitions. Neurourol. Urodynam. 35:283–287, 2016 . © 2015 Wiley Periodicals, Inc.